The influence of self-efficacy in ethical consideration and decision-making process: views from Malaysian Public Relations practitioners - Eyo, Nsini Anselem; Mohd Hasan, Nurul Ain (Public Knowledge Project, 2021)
The study explores factors influencing PR practitioners’ ethical consideration in decision-making process. In line with the theoretical approach of self-efficacy, practitioner’s performances emanate from individual self-efficacy aligned with organization culture and objectives. Thus, self-efficacy inspires individual behavior based upon their belief and capacity to execute or perform actions essential to pro-duce expected results. Based on 20 semi-structured interviews with Malaysian PR practitioners, questions were based on a set of collected and collated reviews of the literature as well as guided by responsible advocacy theory and self-efficacy theory to facilitate the interview process. Data from the interviews were transcribed, coded, and thematically analyzed. Findings of the study indicate that organizational interest, goals, and business focus, corporate politics, boss-influenced clients or stakeholder pressure and practitioners’ personal values were influential factors affecting practitioner’s ethical and decision-making dispositions. Further findings showed that the level of discretions practitioners processed in decision-making process is based on a combination of internal factors like organization business focus and external factors like client needs and pressure. Given that practitioners are bounded by organization laws as employees; it is recommended that independent bodies be put in place other than national public relations associations to serve as a regulator over unethical practices and protection of practitioners against corporate powers.